Transformational Marketing: Linking Marketing and Sustainability - Hossain, Amzad; Marinova, Dora (World Business Institute, 2013)
Current marketing practices promote goods and services irrespective as to what their impacts on the environment and human society are. As this often has serious negative ecological and social consequences, change in practices and better education are required. The paper argues for the need for transformational marketing which links marketing with sustainability values in order to contribute towards mitigating or reversing the environmental and other harm caused by humans because of their poor consumption choices. Such new sustainability approach to marketing would allow to: (1) change the way marketing is perceived; (2) improve its role within society and (3) emphasize the long-term responsibility of business and consumers in relation to the marketed products, services or activities. Incorporating sustainability into education for marketing would inspire marketers to develop a new business ethics that puts global human and ecological values ahead of short-term business profits. Most importantly, such ethics would build the foundations of trust and respect allowing marketing to support only moral and responsible businesses, the benefits from which would be long-term and to broader society.